A rotary permanent magnet magnetic refrigerator based on AMR cycle. (25th May 2016) - Aprea, C.; Cardillo, G.; Greco, A.; Maiorino, A.; Masselli, C.
Abstract: Magnetic refrigeration is an emerging, environment-friendly technology based on a magnetic solid that acts as a refrigerant by magneto-caloric effect (MCE). The reference cycle for magnetic refrigeration is AMR (Active Magnetic Regenerative refrigeration). In order to demonstrate the potential of magnetic refrigeration to provide useful cooling in the near room temperature range, a novel Rotary Permanent Magnet Magnetic Refrigerator (RPMMR) is described in this paper. Gadolinium has been selected as magnetic refrigerant and demineralized water has been employed as regenerating fluid. The total mass of gadolinium (1.20 kg), shaped as packed bed spheres, is housed in 8 regenerators. A magnetic system, based on a double U configuration of permanent magnets, provides a magnetic flux density of 1.25 T with an air gap of 43 mm. A rotary vane pump forces the regenerating fluid through the regenerators. The operational principle of the magnetic refrigerator and initial experimental results are reported and analyzed.